Ground-based Network of NDVI measurements for tracking temporal dynamics of canopy structure and vegetation phenology in different biomes - Soudani, K; Hmimina, G; Delpierre, N; Pontailler, J.-Y.; Aubinet, M; Bonal, D; Caquet, B; de Grandcourt, A; Burban, B; Flechard, C; Guyon, D; GRANIER, a; et al. (Remote Sensing of Environment, 2012)
Plant phenology characterises the seasonal cyclicity of biological events such as budburst, ﬂowering, fructiﬁ- cation, leaf senescence and leaf fall. These biological events are genetically pre-determined but also strongly modulated by climatic conditions, particularly temperature, daylength and water availability. Therefore, the timing of these events is considered as a good indicator of climate change impacts and as a key parameter for understanding and modelling vegetation–climate interactions. In situ observations, empirical or bioclimatic models and remotely sensed time-series data constitute the three possible ways for monitoring the timing of plant phenological events. Remote sensing has the advantage of being the only way of surface sampling at high temporal frequency and, in the case of satellite-based remote sensing, over large regions. Nevertheless, exogenous factors, particularly atmospheric conditions, lead to some uncertainties on the seasonal course of surface reﬂectance and cause bias in the identiﬁcation of vegetation phenological events. Since 2005, a network of forest and herbaceous sites has been equipped with laboratory made NDVI sensors to monitor the temporal dynamics of canopy structure and phenology at an intra-daily time step. In this study, we present recent results obtained in several contrasting biomes in France, French Guiana, Belgium and Congo. These sites represent a gradient of vegetation ecosystems: the main evergreen and deciduous forest ecosystems in temperate climate region, an evergreen tropical rain forest in French Guiana, an herbaceous savanna ecosystem in Congo, and a succession of three annual crops in Belgium. In this paper, (1) we provide an accurate description of the seasonal dynamics of vegetation cover in these different ecosystems (2) we identify the most relevant remotely sensed markers from NDVI time-series for determining the dates of the main phenological events that characterize these ecosystems and (3) we discuss the relationships between temporal canopy dynamics and climate factors. In addition to its importance for phenological studies, this ground-based Network of NDVI measurement provides data needed for the calibration and direct validation of satellite observations and products.
Keywords: Crops; Evergreen and deciduous forests; Ground-based NDVI; Herbaceous savanna; NDVI time-series; Phenology; Tropical rain forest

Sensitivity of water and carbon fluxes to climate changes from 1960 to 2100 in European forest ecosystems - Davi, H; Dufrêne, E; Francois, C; Le Maire, G; Loustau, D; Bosc, A; Rambal, S; GRANIER, a; Moors, E (Agricultural and Forest Meteorology, 2006)
The effects of climate changes on carbon and water ﬂuxes are quantiﬁed using a physiologically multi-layer, process-based model containing a carbon allocation model and coupled with a soil model (CASTANEA). The model is ﬁrst evaluated on four EUROFLUX sites using eddy covariance data, which provide estimates of carbon and water ﬂuxes at the ecosystem scale. It correctly reproduces the diurnal ﬂuxes and the seasonal pattern. Thereafter simulations were conducted on six French forest ecosystems representative of three climatic areas (oceanic, continental and Mediterranean areas) dominated by deciduous species (Fagus sylvatica, Quercus robur), coniferous species (Pinus pinaster, Pinus sylvestris) or sclerophyllous evergreen species (Quercus ilex). The model is driven by the results of a meteorological model (ARPEGE) following the B2 scenario of IPCC. From 1960 to 2100, the average temperature increases by 3.1 8C (30%) and the rainfall during summer decreases by 68 mm (27%). For all the sites, between the two periods, the simulations predict on average a gross primary production (GPP) increase of 513 g(C) m 2 (+38%). This increase is relatively steep until 2020, followed by a slowing down of the GPP rise due to an increase of the effect of water stress. Contrary to GPP, the ecosystem respiration (Reco ) raises at a constant rate (350 g(C) m 2 i.e. 31% from 1960 to 2100). The dynamics of the net ecosystem productivity (GPP minus Reco ) is the consequence of the effect on both GPP and Reco and differs per site. The ecosystems always remain carbon sinks; however the sink strength globally decreases for coniferous (8%), increases for sclerophyllous evergreen (+34%) and strongly increases for deciduous forest (+67%) that largely beneﬁts by the lengthening of the foliated period. The separately quantiﬁed effects of the main variables (temperature, length of foliated season, CO2 fertilization, drought effect), show that the magnitude of these effects depends on the species and the climatic zone
Keywords: canopy scale; carbon sink; climate change; forest ecosystems; Phenology